Implementation of Healthy Lifestyle Through Rhythmic Gymnastics for Village Communities - Wardhani, Rio; Iskandar; Yane, Stephani; Effendi, Awang Roni; Rustanto, Heri; Supriadi, Idris (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2024)
The purpose of community service activities is to provide the village community with guidance on maintaining bodily health by adopting a healthy lifestyle through rhythmic gymnastics. Based on data from the Directorate General of Public Health of the Ministry of Health of the Republic of Indonesia in 2022, the percentage of districts/cities promoting a healthy living movement in West Kalimantan province was 28.6%. This means that the figure has not yet reached the target of the community movement plan set at 40%. The methods provided include: (1) survey stages with partners, (2) coordination with the Village Chief and local tribal leaders, (3) implementation of healthy gymnastics socialization, (4) documentation and publication. The results of the community service (PKM) implementation are considered good and responsive, as conveyed by the PKM team that the enthusiasm of the villagers participating in the socialization of a healthy lifestyle through rhythmic gymnastics for the village community is high among both young and old age groups